The 2022 state elections in Uttar Pradesh and the RSS-isation of the BJP - Chaturvedi, S; Gellner, DN; Pandey, SK (Taylor & Francis, 2023)
Since 2014, the BJP has become increasingly dominant in Uttar Pradesh, India, a state where, as recently as 2012, its vote share had slumped to 15 percent. This paper examines, through ethnographic field research with party workers and others, the reasons for the turnaround in the party’s fortunes. A large part of the answer lies in the increasing strength of BJP party organisation, modelled on an RSS template, as well as the increasing coordination between the RSS and the BJP, with RSS personnel frequently seconded to the BJP. This intense closeness between the RSS and the BJP is a new post-2014 feature, something that did not characterise earlier periods of the BJP in power. A second key factor, building on the BJP’s increased organisational capacity, and one long advocated by the RSS, is the mobilisation of state welfare benefits by the party and the concerted effort to convert welfare recipients, coming from all communities, into supporters. A third key factor, at which the BJP is increasingly adept and where RSS organisational skills provide a significant advantage, is the micromanagement of caste dynamics and religious polarisation as and when required to gain and maintain a political advantage.